Income, personality, and subjective financial well-being: the role of gender in their genetic and environmental relationships - Zyphur, Michael J.; Li, Wen-Dong; Zhang, Zhen; Arvey, Richard D.; Barsky, Adam P. (Frontiers in Psychology, 2015)
Increasing levels of financial inequality prompt questions about the relationship between income and well-being. Using a twins sample from the Survey of Midlife Development in the United States and controlling for personality as core self-evaluations, we found that men, but not women, had higher subjective financial well-being when they had higher incomes. This relationship was due to ‘unshared environmental’ factors rather than genes, suggesting that the effect of income on subjective financial well-being is driven by unique experiences among men. Further, for women and men, we found that core self-evaluations influenced income and subjective financial well-being, and that both genetic and environmental factors explained this relationship. Given the relatively small and male-specific relationship between income and subjective financial well-being, and the determination of both income and subjective financial well-being by personality, we propose that policy makers focus on malleable factors beyond merely income in order to increase subjective financial well-being, including financial education and building self-regulatory capacity.